Modified extended tanh-function method and its applications to the Bogoyavlenskii equation - H.M. Zahran, Emad; M.A. Khater, Mostafa (Applied mathematical modelling, 2016)
In this study, we consider exact traveling wave solutions of the Bogoyavlenskii equation using a modified extended tanh-function method. This method has a broad applicability to many other nonlinear evolution equations in mathematical physics.